2019
DOI: 10.3390/foods8100444
|View full text |Cite
|
Sign up to set email alerts
|

Taste Sensitivity Is Associated with Food Consumption Behavior but not with Recalled Pleasantness

Abstract: As taste perception varies between individuals, it might be important in explaining food consumption behavior. Previous studies have focused on sensitivity to the bitter tastant PROP (6-n-propylthiouracil) concerning eating with little attention paid to other tastants. For the first time, connections between food consumption behavior, pleasantness, and taste sensitivity are studied with five taste modalities. Sensitivity to bitterness, sourness, umami, saltiness, and sweetness as well as an overall taste sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 47 publications
(82 reference statements)
2
30
0
Order By: Relevance
“…Previous research has indicated associations between taste sensitivity and food consumption behavior [33]. Specifically, increased taste sensitivity was associated with avoidance of coffee in this questionnaire-based study.…”
Section: Discussionsupporting
confidence: 54%
“…Previous research has indicated associations between taste sensitivity and food consumption behavior [33]. Specifically, increased taste sensitivity was associated with avoidance of coffee in this questionnaire-based study.…”
Section: Discussionsupporting
confidence: 54%
“…According to Puputti et al [89], taste sensitivity influences food consumption but there is no effect between taste sensitivity and food liking, also corroborating Tepper's study [10]. This association was investigated for the first time by Pangborn and Pecore [90] who aimed to understand the correlation between DT and hedonic response.…”
Section: Children's Taste Sensitivity and Food Likingmentioning
confidence: 61%
“…Prolonged umami consumption (through MSG supplemented broths) has been shown to decrease umami taste perception in women, and desire and intake of savory foods at an ab libitum meal in both sexes (Noel, Finlayson, & Dando, 2018). Lower umami taste sensitivity has been associated with lower consumption of seaweed and sugar (Kubota, Toda, & Nagai‐Moriyama, 2018), lower vegetable consumption, and higher salty‐savory food consumption in comparison to more sensitive participants (Puputti, Hoppu, & Sandell, 2019). Recent research has found that genetic variations in umami taste receptors are associated with increased protein consumption (variation on the TAS1R3 gene), and energy and fat consumption (variation on the TAS1R1 gene) of umami‐ tasting foods during an ab libitum buffet study (Han, Keast, & Roura, 2018).…”
Section: Resultsmentioning
confidence: 99%